Ética e bioética: o que os alunos do sexto ano médico têm a dizer - Camargo, Aline [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP]; Morita, Ione [UNESP] (FapUNIFESP (SciELO), 2014)
Ethical and bioethical training is essential to the humanization of care as recommended by Brazilian health policy and tothe development of a critically-minded professional. Recent studies have shown that ethics and bioethics are afforded limited class hours in medicinecourses. Their importance is also noteworthy in light of the high number of complaints against doctors that are received by the Regional Medical Councils. This study aimed at identifying the perception of sixthyear medical students concerning bioethical issues. Self-applicable questionnaires containing open-ended and closed-ended questions were presented to the students. Seventy out of ninety registered students answered them. Students considered curricular academic training and practical examplesgiven by teachers as important sources for learning ethics and bioethics. On the other hand, dissatisfaction was expressed regarding how the topic is approached in undergraduate courses. The study highlighted shortcomings in education which must be resolved in order to enhance ethical training and medical practice.

A formação ética e bioética é fundamental para a humanização do atendimento preconizada pela polí- tica de saúde no Brasil e para o desenvolvimento de um profissional crítico.Estudos recentes revelam que Ética e Bioética têm carga horária restrita nos cursos médicos. Ressalta-se, ainda, sua importância diante do grande número de denúncias contra médicos recebido pelos Conselhos Regionais de Medicina. O objetivo deste trabalho foi identificar a percepção sobre questões éticas e bioéticas dos alunos do sexto ano médico, que, portanto, logo estariam ingressando no mercado de trabalho. Foram entregues questionários autoaplicáveis com perguntas abertas e fechadas aototal de 93 matriculados, dos quais 70 responderam. Os alunos consideraram a formação curricular acadêmica e o exemplo prático dos professores como importantes fontes de aprendizado da Ética e Bioética. Este fato contrapõe-se à insatisfação quanto à forma de abordagem do tema na graduação. O estudo tornou evidente a existência de deficiências no ensino que devem ser supridas a fim de aprimorar a formação ética e a prática médica.
Ethics and bioethics: what sixth year medical students have to say
Keywords: Ethics; Bioethics; Medical ethics; Medical students; Medical education; Ética; Bioética; Ética médica; Estudantes de medicina; Educação médica